Characterization of electrostatic discharge threshold voltage of phase-shift mask reticle - Harriman Razman; Azmi Awang Md Isa; Mohamad Kadim Suaidi; Mohd Azizi Chik (International Journal of Electrical and Computer Engineering (IJECE), 2022)
A reticle is a stencil used in lithography process for forming integrated circuit (IC) on silicon substrate. It consists of a thin (100 nm) coating of masking metallic patterned (features) with critical dimension (CD) of nanometers on a thicker quartz substrate. The features can be damaged by electrostatic discharge (ESD) when exposed to the environment electrostatic charge and caused deformed IC and eventually device difunctional. Semiconductor equipment materials industry (SEMI) standard established the allowable electrostatic charge on reticle based on the characterization of ESD threshold voltage on binary reticle. However, there is another type of reticle which is phase-shift mask (PSM), has not been characterized for its ESD threshold voltage. A direct current (DC) voltage is applied directly to the structures with CD of 80 nm, 110 nm, and 160 nm. The surface current is recorded at all levels of stress from 1 to 100 V. The current–voltage (IV) curve and physical inspection results for each cell are then reviewed and classified. The results yielded which no electric field induced migration (EFM) defect and breakdown voltage occurred at any of the structures. The cathode’s metal work function has been identified as the factor that influences the PSM reticle ESD threshold voltage.